KELANGSUNGAN HIDUP DAN PERTUMBUHAN IKAN GABUS(Channa striata) PADA BERBAGAI MODIFIKASI PH MEDIA AIR RAWA YANG DIBERI SUBSTRAT TANAH - Jimmi Astria; Marsi .; Mirna Fitrani (Jurnal Akuakultur Rawa Indonesia, 2013)
ABSTRACT This current research aimed to find out survival and growth of snakehead fish (Channa striata) reared in different pH media modification and to find out the optimum pH for rearing. Research was conducted in Aquaculture Laboratory, Aquaculture Program Study, Agriculture Faculty, Sriwijaya University from October toNovember2012. This researchcurrent used completely randomized design with  five treatments and three replications. The treatments were P0 (without treatments), P1 (decreased from pH 5.75 to 3.00), P2 (decreased from pH 5.75 to 4.00), P3 (decreased from pH 5.75 to 5.00) and  P4 (increased from pH 5.75 to 6.00).   The result of this  current research showed that the best  survival rate and growth based on regression analysis growth and weight total biomass end was found for P3 treatment (decreased from pH 5.75 to 5.00). Result of water physical and chemical measered were dissolved oxigen 4.32-4.77 mg.L-1, temperature 26-280C, and amonia 0.0030-0.1281 mg.L-1. Keywords : Channa striata, Ikan gabus, pH